Geochemical Characterisation of Strategic Elements (Li, Co, Ni, Cu, Ga, Ge, and REEs) in Bottom Ash from the Thermal Power Plant (Afşin-Elbistan, Türkiye) - Kalender, Leyla; Kara, Hatice; Erturk, Mehmet Ali; Yalcin, Cihan; Turan, Mehmet Deniz; Sutcu, Emine Cicioglu (Mdpi, 2025)
This study investigates the concentrations and geochemical behaviour of strategic elements-including Li, Co, Ni, Cu, Ga, Ge, rare earth elements (REEs), and yttrium (Y)-in bottom ash samples from the Af & scedil;in-Elbistan thermal power plant, T & uuml;rkiye. Thirty bottom ash samples were analysed, revealing average & sum;LREE and & sum;HREE concentrations of 86.3 mu g/g and 3.3 mu g/g, respectively, resulting in an L/H ratio of 24.9, indicating pronounced enrichment in light REEs. The total & sum;REE + Y concentration (111 mu g/g) is comparable to the background value for coal but approximately 1.5 times lower than those reported for average Chinese coals and the upper continental crust (UCC). REE contents significantly exceed those of sedimentary (5.36 mu g/g), mafic (16.77 mu g/g), and felsic (3.60 mu g/g) rocks. Elevated Li (30.5 mu g/g) and Ni (114.4 mu g/g) concentrations point to a mafic magmatic source, whereas Cu (28.7 mu g/g) likely originates from basic volcanic rocks such as those of the Da & gbreve;l & imath;ca Complex and the Kemaliye Formation. Chondrite-normalised REE patterns show Dy depletion relative to mafic rocks and Ho depletion compared to sedimentary rocks. Positive delta Eu anomalies (>1) support a mafic or UCC provenance, while slightly positive delta Ce values indicate hydrothermal leaching influences. The co-precipitation of Ce with Ca-Mg hydroxides and clay minerals in coal-bearing lacustrine sediments is suggested. Ga enrichment is attributed to aluminium-rich clay minerals and organic matter. Overall, these geochemical signatures reflect combined inputs from hydrothermal leaching and volcanic weathering within a coal-bearing lacustrine environment.
Keywords: bottom ash; strategic elements; rare earth elements (REEs); thermal power plant